Keratin films for ocular surface reconstruction: Evaluation of biocompatibility in an in-vivo model. (February 2015) - Borrelli, Maria; Joepen, Nadine; Reichl, Stephan; Finis, David; Schoppe, Martin; Geerling, Gerd; Schrader, Stefan
Abstract: Amniotic membrane (AM) transplantation is the clinical standard for ocular surface reconstruction, however recently keratin film (KF) has been proposed as an alternative material. Aim of the current study was to evaluate corneal biocompatibility of KF in a rabbit model. Forty-six New Zealand white rabbits underwent dissection of a corneal intrastromal pocket in which an AM or KF implant was inserted and observed for 10 days and for 4 weeks. Half of animals received topical steroids, while the other half were left without. At the end of the follow-up clinical and histology examinations were performed to evaluate transparency, inflammation and degradation. After 10 days the clinical and the histology results appeared to be comparable in KF implanted eyes treated with and without steroids. After 4 weeks, comparable clinical results were observed in all KF implanted eyes, while the inflammation score was lower in non-steroid compared to steroid treated eyes along with a higher degradation rate of the keratin films. In conclusion, keratin films from human hair show a good biocompatibility and transparency in vivo. The administration of topical steroids seems to slow down implant degradation which might be important for the modulation of tissue integration and matrix regeneration.